Study on the annealing-dependent photoluminescence properties of SnO2 cluster-system structures - Zhu, Yunqing; Chen, Yiqing; Zhang, Xinhua (European Journal of Chemistry, 2011)
SnO2 cluster-system structures were synthesized via a two-step temperature-rising thermal evaporation method with short oxidation time. Field emission scanning electron microscopy, X-ray diffraction and transmission electron microscopy were used to characterize the morphological and structural feature of the product as nanowire cluster and nanoparticle cluster. The photoluminescence spectra exhibit that, as annealing time in air increases, the intensity of the newly found strong ultra-violet emission decreases while the green emission is increased. Raman spectrum and X-ray photoelectron spectroscopy investigations reveal that the relatively decreasing intensity was dominated by the increasing oxygen vacancy. Further calculation based on the SnO2 crystal lattices with H2O molecules at different steps in evaporation process was performed. The result of this calculation confirms that, rather than the influence of H2O molecules from air, the decreasing intensity is the result of the combined action of the formation of oxygen vacancy and the energetic oxygen compensation in annealing treatment.